Hypoxia-Induced miR-137 Inhibition Increased Glioblastoma Multiforme Growth and Chemoresistance Through LRP6 - Li, Dong-Mei; Chen, Qiu-Dan; Wei, Gui-Ning; Wei, Jie; Yin, Jian-Xing; He, Jun-Hui; Ge, Xin; Shi, Zhu-Mei (Frontiers in Oncology, 2021)
Purpose: Glioblastoma multiforme (GBM) is one of the deadliest tumors, which is involved in numerous dysregulated microRNAs including miR-137. However, the mechanism of how miR-137 suppression associated with cancer progression and chemoresistance still remains to be elucidated. Methods: Quantitative reverse transcriptase-PCR (qRT-PCR), DNA methylation analysis, cell proliferation assay, flow cytometric analysis, invasion assay, in situ tumor formation experiment were performed to test the expression levels and functions of miR-137 in GBM. Bioinformatics analysis, luciferase reporter assay, qRT-PCR, immunoblotting, immunofluoresence and immunohistochemistry assay were used to identify and verify the target of miR-137. Results: We found that miR-137 was down-regulated in primary and recurrent GBM compared with traumatic brain tissues. Overexpression of miR-137 inhibited cell proliferation and invasion in GBM, promoted cell apoptosis and enhanced cell chemosensitivity to temozolomide (TMZ) through blocking the expression of epithelial-mesenchymal transition (EMT)-related genes by directly targeting low-density lipoprotein receptor-related protein 6 (LRP6). Forced expression of LRP6 cDNA without its 3’-UTR region partly restored the effects of miR-137 in vitro and in vivo. Intratumoural hypoxia-induced miR-137 methylation was responsible for the miR-137 suppression, leading to the cell chemoresistance and poor prognosis of GBM. Conclusions: Intratumoural hypoxia-induced miR-137 suppression increased GBM cell chemoresistance to TMZ on proliferation, apoptosis and invasion by regulating EMT-related genes expression through Wnt/β-catenin signaling pathway via LRP6.